Tair Ababil : Perspektif Muhammad Abduh dan Wahbah az-Zuhaili - Muhammad Azmi; Akhmad Dasuki; Ade Afriansyah (Syams: Jurnal Kajian Keislaman, 2020)
In interpreting “Tair Ababil”, there are many differences in the various narrations regarding the meaning (definition) of Tair Ababil. Some interpret it rationally and some interpret suprational. The problem examined in this article is: what is meant by Tair Ababil in Qur’an, and how do Muhammad Abduh and Wahbah az-Zuhaili interpret the Tair Ababil? The type of research used in this paper is library research using a qualitative approach. The methods used in this research are thematic method (al-dirasah al-maudhu’iyyah) and comparison method (Muqaran) with descriptive-analysis and comparative-analysis data analysis techniques. The authors concludes, in Qur’an, when mentioning birds with lapaz “tair”, the context is birds in general, whereas when mentioning birds specifically, Qur’an will directly mention names such as “guraban” and “hud-hud”. Muhammad Abduh interpreted “Tair Ababil” as flies, mosquitoes and even microbes, which carry smallpox disease while Wahbah az-Zuhaili interpreted “Tair Ababil” as a group of the smallest black birds carrying stones that cause smallpox. Muhammad Abduh and Wahbah az-Zuhaili have differences and similarities in interpreting “Tair Ababil”, differing in the method of interpretation of Muhammad Abduh with ra’yu and Wahbah az-Zuhaili with riwayah. The same in interpreting the intermediary Tair Ababil destroying Abrahah and his troops, namely the spread of smallpox brought by Tair Ababil.